A comparative genome analysis of Rift Valley Fever virus isolates from foci of the disease outbreak in South Africa in 2008-2010 - Maluleke, Moabi R.; Phosiwa, Maanda; Schalkwyk, Antoinette van; Michuki, George N.; Lubisi, Baratang A.; Kegakilwe, Phemelo S.; Kemp, Stephen J.; Majiwa, Phelix A.O. (Public Library of Science, 2019)
Rift Valley fever (RVF) is a re-emerging zoonotic disease responsible for major losses in livestock production, with negative impact on the livelihoods of both commercial and resource-poor farmers in sub-Sahara African countries. The disease remains a threat in countries where its mosquito vector thrives. Outbreaks of RVF usually follow weather conditions which favour increase in mosquito populations. Such outbreaks are usually cyclical, occurring every 10–15 years. Recent outbreaks of the disease in South Africa have occurred unpredictably and with increased frequency. In 2008, outbreaks were reported in Mpumalanga, Limpopo and Gauteng provinces, followed by 2009 outbreaks in KwaZulu-Natal, Mpumalanga and Northern Cape provinces and in 2010 in the Eastern Cape, Northern Cape, Western Cape, North West, Free State and Mpumalanga provinces. By August 2010, 232 confirmed infections had been reported in humans, with 26 confirmed deaths.To investigate the evolutionary dynamics of RVF viruses (RVFVs) circulating in South Africa, we undertook complete genome sequence analysis of isolates from animals at discrete foci of the 2008–2010 outbreaks. The genome sequences of these viruses were compared with those of the viruses from earlier outbreaks in South Africa and in other countries. The data indicate that one 2009 and all the 2008 isolates from South Africa and Madagascar (M49/08) cluster in Lineage C or Kenya-1. The remaining of the 2009 and 2010 isolates cluster within Lineage H, except isolate M259_RSA_09, which is a probable segment M reassortant. This information will be useful to agencies involved in the control and management of Rift Valley fever in South Africa and the neighbouring countries.